First trimester ultrasound features of X-linked Opitz syndrome and early molecular diagnosis: case report and review of the literature. (17th September 2021) - Sarno, Laura; Maruotti, Giuseppe Maria; Izzo, Antonella; Mazzaccara, Cristina; Carbone, Luigi; Esposito, Giuseppina; Di Cresce, Marco; Saccone, Gabriele; Sirico, Angelo; Genesio, Rita; Mollo, Nunzia; Martinelli, Pasquale; et al.
Abstract: X-linked Opitz G/BBB syndrome (XLOS) is a multiple congenital disorder inherited in an X-linked manner. XLOS may be suspected, in prenatal age, on the basis of sonographic findings in the second and/or third trimester of gestation. Pathogenetic variants in MID1 gene have been reported in individuals with XLOS. Prenatal genetic testing is offered for pregnancies at risk, in which the mutation in the family has been identified. To date no cases of prenatal diagnosis, based on first-trimester ultrasound data, have been reported. We present a case of a fetus at 12 gestational weeks with ultrasound multiple anomalies, including increased nuchal translucency, heart defects, cleft lip and palate, enlarged fourth ventricle absence of ductus venosus and family hystory of XLOS. The genetic prenatal test detected the c(0).1286-1G > T mutation of MID1 gene. Data about prenatal ultrasonographic findings consistent with XLOS are limited to second and third trimester. This is the first case reporting ultrasound detectable midline defects suggestive of XLOS as early as the first trimester of gestation. This case also suggests that when multiple anomalies are detected in a fetus with normal chromosomal structure, the possibility of a monogenic disorder must be considered.